Analisis Semiotika Makna Sabar Dan Syukur Dalam Film Gadis Diruang Tunggu - Sulistiani, Umi; Syarifudin, Achmad; Hamandia, Muhammad Randicha (CV. ITTC INDONESIA, 2023)
Film in a narrow sense is the presentation of images via a wide screen, but in a broader sense it can also include those broadcast on TV. The film The Girl in the Waiting Room is the result of the reality of people's lives in general. This research is entitled